Metaplastic breast cancers and triple-negative breast cancers of no special type: are they prognostically different? A systematic review and meta-analysis. Issue 5 (15th December 2021) - Corso, Giovanni; D'Ecclesiis, Oriana; Magnoni, Francesca; Mazzotta, Erica; Conforti, Fabio; Veronesi, Paolo; Sajjadi, Elham; Venetis, Konstantinos; Fusco, Nicola; Gandini, Sara
Abstract : Background and aims: Metaplastic breast cancer (MBC) and triple-negative (TN) BC of no special type are often confounded with each other in terms of survival and prognosis. In this systematic study and meta-analysis, we evaluated the prognosis of each of these two different diagnoses. Methods: We conducted a systematic literature search and review using the MOOSE guidelines, through PUBMED database, the Ovid MEDLINE database, and the ISI Web of Science Citation Index Expanded (SCI Expanded). Overall survival (OS) and disease-free survival (DFS) were the main outcomes considered. Results: Our review eventually selected six independent studies, with a total of more than 59 519 patients. MBC was found to associate with worse OS compared to TNBC of no special type, with a significant 40% increased risk of death [summary hazard ratio (SHR) = 1.40, 95% confidence interval (CI): 1.30–1.50]. We found neither heterogeneity ( I 2 = 0%) nor evidence of publication bias ( P = 0.82 and P = 0.49 by Begg's and Egger's test, respectively) between studies. No statistically significant difference was found between MBC and TNBC of no special type in terms of DFS (SHR = 1.17, 95% CI: 0.80–1.71). Conclusion: This study demonstrates that TNBC of no special type and MBC have comparable DFS, although the latter presents a significantly worse prognosis in terms of OS. Despite DFS being similar in both subtypes, this did not result in significant OS benefits, with MBC score being the worse of the two diseases.